Understanding the purchasing intentions of Korean skincare products among university students in Indonesia - Santoso, Adi; Yuliarta, Refina Dwi; Safitri, Unna Ria; Anggorowati, Luki Sri; Rahayu, Listyowati Puji (Jurnal Ekonomi dan Bisnis, 2024)
This study investigates the factors influencing the purchase intention and consumer purchase decisions of Korean skin care products. Three factors, namely the Korean wave, social media, and reference groups, were included in this study. The number of samples used was 300 students with certain criteria using a purposive sampling technique. Data were analyzed using the PLS-SEM method using Smart PLS 3.0 software. The results showed that the Korean wave, social media, and reference groups significantly and positively affected consumer purchase intention. Furthermore, this study also found a significant and positive influence between social media and purchasing decisions. Meanwhile, the Korean wave and reference group variables do not significantly impact purchasing decisions. In addition, buying interest influences consumer purchasing decisions. The conclusion of this study proves that Korean wave social media and reference groups affect consumer purchase intention behavior. Social media influences consumer purchasing decisions, while the Korean wave and reference groups affect purchasing decisions. Furthermore, the study results show that purchase intention can mediate the relationship between the Korean wave, social media, and reference groups on purchasing decisions.